2013
DOI: 10.4028/www.scientific.net/amm.315.517
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Emissions Characteristics of Diesel Engine Fuelled by Biodiesel Derived from Palm Oil

Abstract: Bio fuels based on vegetable oils offer the advantage being a sustainable, annually renewable source of automobile fuel. Despite years of improvement attempts, the key issue in using vegetable oil-based fuels is oxidation stability, stoichiometric point, bio-fuel composition, antioxidants on the degradation and much oxygen with comparing to diesel gas oil. Thus, the improvement of emissions exhausted from diesel engines fueled by biodiesel derived from palm oil is urgently required to meet the future stringent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…The high injection pressure is because of the better mixing achievable [27]. The different types of injectors with different geometries, produces different amount of losses in fuel flow rate based on these different injectors [29,30]. Different types of injectors have different pattern nozzle, the nozzle concept is that after the closing of the nozzle in high pressure part of the combustion process, the fuel is stored in the injector holes.…”
Section: Fuel Injection Pressure and Nozzle Characteristics Powermentioning
confidence: 99%
“…The high injection pressure is because of the better mixing achievable [27]. The different types of injectors with different geometries, produces different amount of losses in fuel flow rate based on these different injectors [29,30]. Different types of injectors have different pattern nozzle, the nozzle concept is that after the closing of the nozzle in high pressure part of the combustion process, the fuel is stored in the injector holes.…”
Section: Fuel Injection Pressure and Nozzle Characteristics Powermentioning
confidence: 99%
“…However, the application of the BDF in the diesel engines offer not only attractive and more economical fuel but also creates problems of higher emissions compared with petroleum based diesel. BDF diesel engines still have problem of emitting NOx and Particulate Matter (PM) into the atmosphere because of the oxidation stability, cetane number, stoichiometric point, bio-fuel composition and antioxidants on the degradation extremely viscous [5][6]. Thus, the improvement of emissions exhausted from BDF engines is urgently required to meet the future stringent emission regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, heat recovery process starts when fuel-oxidation generates heat. There were many studies on the fuel-air premixing that resulting from air entrainment which linked to the improvement of exhaust emissions [1][2][3]. Ishiyama et al [4] has reported that the ignition process in diesel combustion, oxidation begins very early during ignition delay period and its supplies heat to the spray and causes cracking and gasification of fuel.…”
Section: Introductionmentioning
confidence: 99%